Using several intelligences for complex industrial process monitoring: Detection and diagnosis - Rezki Nafissa (IOEM 2016 International Conference on Industrial Engineering and Operations Management At Kuala Lumpur, Malaysia, 2016)
The objective of the current paper is to present an intelligent system for complex process monitoring, based on artificial intelligence technologies. This system aims to realise with success some complex process monitoring tasks that are: detection, diagnosis. For this purpose, the development of a multi-agent system that combines multiple intelligences such as: multivariate control charts, neural networks, has became a necessary. The proposed system is evaluated in the monitoring of the complex process Tennessee Eastman Process.